Body Composition May Affect Sperm Concentration and Total Motile Sperm Count in Male Infertility with Varicocele - Rizal Dicky Moch; Setiawan R. Jajar; Septiyorini Nandia; Azyan Muhammad; Putra Farhan Sakundirasta; Al Fathdry Muhamad Hafiz (BIO Web of Conferences)
Obesity is a global health problem with an ever-increasing prevalence in society. This condition can be a risk factor for developing other health issues, including infertility. This study aims to examine the relationship between body composition and total motile sperm count (TMSC) in infertile male patients with varicocele. A cross-sectional study was conducted on 37 infertile male patients diagnosed with varicocele based on physical examination. The study examined the effect of body composition parameters (Body Mass Index, body fat percentage, visceral fat level, and waist circumference) on sperm parameters. The results were tabulated and analyzed using the Statistical Package for the Social Sciences (SPSS) software. It was identified that body fat percentage and visceral fat level significantly affect sperm concentration and TMSC (p<0.05). However, BMI and waist circumference did not show a statistically significant effect on sperm parameters. This study suggests that BMI alone cannot always be used as an indicator of sperm quality and quantity in infertile men. Therefore, examination of other body composition parameters should be considered when conducting sperm assessments in infertile men.